Virtual Reality App (SI-VIGUR) to Improve Sleep Quality among Older Adults in Nursing Homes - Martini, Sri; Aguscik, Aguscik; Farama, Dodi Aflika; Somad, Abdul; Hartati, Sri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Sleep disturbances are common among older adults, especially those residing in nursing homes, and can significantly affect their quality of life and overall well-being. Non-pharmacological interventions, such as guided imagery and virtual reality (VR), have shown promise in improving sleep quality by promoting relaxation and reducing cognitive arousal. The SI-VIGUR (Virtual Reality Guided Imagery) app combines VR technology with guided imagery to offer a therapeutic solution for improving sleep in older adults. This study aimed to evaluate the effectiveness of the SI-VIGUR VR app in improving sleep quality among older adults in nursing homes. This study aimed to evaluate the effectiveness of the Virtual Reality Guided Imagery (SI-VIGUR) application in improving sleep quality among older adults in nursing homes in Palembang City, South Sumatra, Indonesia, in 2024. Using a quasi-experimental design with pre- and post-tests, 80 participants aged 60 or older with sleep disturbances were selected. They received 15-minute SI-VIGUR sessions three times a week for 1 months. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Participants in the experimental group showed a significant improvement in sleep quality, as evidenced by a decrease in their PSQI scores (from 14.20 ± 1.86 to 7.31 ± 2.81). The intervention group demonstrated a marked reduction in poor sleep quality, with a higher percentage of individuals reporting fair or good sleep quality after the intervention compared to before. These findings were statistically significant (p = 0.0001), confirming the effectiveness of the SI-VIGUR app. The SI-VIGUR VR app proved to be an effective non-pharmacological intervention for improving sleep quality among older adults in nursing homes. The results suggest that VR-guided imagery can significantly reduce sleep disturbances, offering a promising solution for enhancing the well-being of older adults in institutional settings.